Single Nucleotide Polymorphism Genotypes of the Follicle Stimulating Hormone Gene Associated with Egg Production from Tegal and Magelang Ducks with Their Resulting Reciprocal Crosses - Purwantini , Dattadewi; Santosa, Setya Agus; Ismoyowati (International Journal of Poultry Science, 2017)
Background and Objective: The egg productivity of Indonesian local duck is higher than that of other local poultry. Follicle stimulating hormone (FSH) is part of the glycoprotein hormone that plays an important role in stimulating egg production by the ovaries. The FSH gene can be identified based on its nucleotide sequence by using the single nucleotide polymorphism (SNP) technique. The aim of this study was to identify SNPs of the FSH gene and investigate the SNP associations with egg production characteristics in two native Indonesian ducks, including the Tegal duck, the Magelang duck (F0) and reciprocal crosses named Gallang and Maggal (F1). Materials and Methods: This study used 200 ducks, comprising 50 of each breed. FSH gene amplification used the forward primer FSH-AnasPF: L 556 5’- TTCAGGCCTCCCCTACTTCT-3’ and reverse FSH-AnasPR: H 820 5’- GTGCTGCAAGGCTTTTTAGG-3’. The SNP was determined according to the BioEdit v7.2.0 program through the ClustalW menu (accessory application). Allele and genotype frequencies were applied to observe the Hardy-Weinberg (H-W) equilibrium. The SNP genotype gene FSH associated with egg production was subject to quantitative trait loci (QTL) analysis. Results: The research successfully amplified a 264-bp PCR product to identify SNPs. SNPs were found at 700-nt (c.700T>C) and 701-nt (c.701G>A) in the H-W equilibrium. The characteristics of egg production were affected by a double allele C (dominant) and A (recessive). Therefore 3 genotype pairs CC, CA and AA for all populations determined the high, medium or low egg production. The effects of the average gene C (α1) in the Tegal duck, Magelang duck and reciprocal crosses were 15.25; 13.74; 12.23 and 11.01, respectively, whereas gene A (α2) had a negative effect and led to values of -12.99 -14.30, -11.29 and -11.46, respectively. Conclusion: SNP genotypes of the FSH gene in Tegal, Magelang and the reciprocal cross ducks were polymorphic and associated with egg production characteristics. SNP genotypes of the FSH gene (SNP c.700T>C and SNP c.701G>A) were viable candidates for marker assisted selection (MAS) to determine the egg productivity of Indonesian local ducks.